We have to solve f(x) = 2x^2 -x -15 by factoring.

Now we see that -1 can be written as 5 - 6 = -1. Here 5*-6 = -30.

f(x) = 2x^2 -x -15 = 0

=> 2x^2 - 6x + 5x - 15 = 0

=> 2x(x - 3) + 5(x - 3) = 0

=> (2x + 5)(x - 3) = 0

For 2x + 5 = 0

=> x = -5/2

And for x - 3 = 0

=> x= 3

**Therefore x is equal to -5/ 2 and 3.**

Given the function f(x) = 2x^2 -x -15

We need to solve for x by factoring.

First we have a quadratic equation. Then we can simplify into two factor.

==> f(x) = 2x^2 -x -15

We will try and determine one of the roots.

We will substitute with x=3.

==> f(3) = 2*9 0-3 -15 = 0

==> X=3 is one of the roots.

Then (x-3) is one of the factor.

==> f(x) = (x-3) * R(x)

Now, to find the other factor, we will divide f(x) by (x-3).

**==> f(x) = (x-3)(2x+5)**

**==> x1= 3 **

**==> x2= -5/2**

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now